Driving gene-engineered T cell immunotherapy of cancer - Johnson, Laura A; June, Carl H (Cell research, 2017)
Chimeric antigen receptor （CAR） gene-engineered T cell therapy holds the potential to make a meaningful differ- ence in the lives of patients with terminal cancers. For decades, cancer therapy was based on biophysical parameters, with surgical resection to debulk, followed by radiation and chemotherapy to target the rapidly growing tumor cells, while mostly sparing quiescent normal tissues. One breakthrough occurred with allogeneic bone-marrow transplant for patients with leukemia, which provided a sometimes curative therapy. The field of adoptive cell therapy for sol- id tumors was established with the discovery that tumor-infiltrating lymphocytes could be expanded and used to treat and even cure patients with metastatic melanoma. Tumor-specific T-cell receptors （TCRs） were identified and engineered into patient peripheral blood lymphocytes, which were also found to treat tumors. However, these were limited by patient HLA-restriction. Close behind came generation of CAR, combining the exquisite recognition of an antibody with the effector function of a T cell. The advent of CD19-targeted CARs for treating patients with multiple forms of advanced B-cell malignancies met with great success, with up to 95% response rates. Applying CAR treat- ment to solid tumors, however, has just begun, but already certain factors have been made clear： the tumor target is of utmost importance for clinicians to do no harm; and solid tumors respond differently to CAR therapy compared with hematologic ones. Here we review the state of clinical gene-engineered T cell immunotherapy, its successes, chal- lenges, and future.